Vigorous physical activity in relation to family affluence: time trends in Europe and North America - Sigmundová, Dagmar; Sigmund, Erik; Ṭesler, Riḳi; Ng, Kwok W.; Hamrik, Zdenek; Mathisen, Frida Kathrine Sofie; Inchley, Jo; Bucksch, Jens (International journal of public health, 2019)
The aim of the study was to determine secular trends in vigorous physical activity (VPA) among adolescents in relation to family affluence across 34 countries.
Published: 05 July 2019
Gesehen am 21.04.2020